2007
DOI: 10.1086/522483
|View full text |Cite
|
Sign up to set email alerts
|

A 2MASS All‐Sky View of the Sagittarius Dwarf Galaxy. V. Variation of the Metallicity Distribution Function along the Sagittarius Stream

Abstract: We present reliable measurements of the metallicity distribution function (MDF) at different points along the tidal stream of the Sagittarius (Sgr) dwarf spheroidal (dSph) galaxy, based on high resolution, echelle spectroscopy of candidate M giant members of the Sgr system. The Sgr MDF is found to evolve significantly from a median [Fe/H] ∼ −0.4 in the core to ∼ −1.1 dex over a Sgr leading arm length representing ∼2.5-3.0 Gyr of dynamical (i.e. tidal stripping) age. This is direct evidence that there can be si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
190
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(213 citation statements)
references
References 59 publications
20
190
3
Order By: Relevance
“…The SF then continues, but at a lower rate, until it is negligible. It has been claimed though that dynamical interactions could remove preferentially the most metal-poor stars of dwarf galaxies (as it has been shown for Sagittarius - Monaco et al 2007;Chou et al 2007), thus modifying the observed present-day SMD. This point, if it were present in the dSph galaxies Leo 1 and Leo2, would imply a higher fraction of metal-poor stars and broader SMDs.…”
Section: Discussionmentioning
confidence: 91%
“…The SF then continues, but at a lower rate, until it is negligible. It has been claimed though that dynamical interactions could remove preferentially the most metal-poor stars of dwarf galaxies (as it has been shown for Sagittarius - Monaco et al 2007;Chou et al 2007), thus modifying the observed present-day SMD. This point, if it were present in the dSph galaxies Leo 1 and Leo2, would imply a higher fraction of metal-poor stars and broader SMDs.…”
Section: Discussionmentioning
confidence: 91%
“…Stars in the Sgr dSph stream appear to be slightly less metal rich than those in the main body, with metallicity gradients along the stream (Bellazzini et al 2006b;Clewley & Jarvis 2006;Monaco et al 2007;Chou et al 2007). This would not be unexpected if the most metal poor stars were located in the outskirts of Sgr dSph and then subject to the tidal interaction with the MW.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of Sgr stars show peculiar abundance patterns compared to those of nominal Milky Way (MW) stars (left panel, Fig. 1) and, as a group, form a coherent picture of chemical enrichment of the Sgr dwarf spheroidal (dSph) from [Fe/H] = −1.4 to solar abundance (Chou et al 2007(Chou et al , 2009 , Fig. 1); these relative shifts reflect the faster and/or more efficient chemical evolution of Sgr compared to the other satellites.…”
Section: Resultsmentioning
confidence: 99%